THE SOCIO-CULTURAL DIMENSIONS OF SCIENCE - Purwadi, Y. Slamet (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2008)
Logical positivism and empiricism embody the scientific spirit thatputs science autonomous from culture and society. This can bequestioned from a cultural perspective, which accommodates thevarious contexts of human knowledge. In this perspective, scienceas a system of human knowledge is deeply rooted and colored bythe socio-cultural context.